Síntomas de ansiedad y su correlación con el consumo de sustancias en trabajadores de Jornada nocturna de la ciudad de Loja - Urgilés Arévalo, Gabriel Rodrigo (2019)
It results easy to enlist works around us that implies at least one sleeplessness night per week, anxiety as a natural process, adapts the person to the environment, it appears as unpleasant symptoms such as nervousness, tiredness, dizziness, tachycardia, feeling faint, breathing difficulties, sweating, trembling, worry, insomnia, difficulty concentrating and hypervigilance. (Sarason & Sarason, 2006). “Substance use” which it is refer to ingestion of psychoactive substances in moderate amounts that does not significantly interfere with personal functioning (Barlow & Durand, 2008), it takes side in moments where the body requires aid to get over an adverse situation. Here we will learn the anxiety manifestations and the substances that “helps” to maintain performance in night shift workers. This study purpose lies in delimit the correlation between anxiety and substance use in night shift workers in Loja city. Present cross-sectional study was made through an interview and the application of two tests: Anxiety Situations and Responses Inventory (ISRA) and The Alcohol, Smoking and Substance Involvement Screening Test (ASSIST); in which participated 108 night-shift workers among we may enlist drivers, taxi drivers, liquor store attendants, waiters, cookers, bar’s administrators, nurses, gas station attendants, security guards. Results obtained shows a negligible positive correlation in substance use and anxiety (Rho Spearman=0,262; p=0,006) in all interviewed people (n=108). Keywords: anxiety, psychoactive substances, night workers.